Resin composition for insulating stator core

JP7639854B2Active Publication Date: 2025-03-05SUMITOMO BAKELITE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023102250
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-06-22
Publication Date
2025-03-05
Estimated Expiration
2038-12-10

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、樹脂組成物を充填する際の作業性、樹脂の充填性および樹脂の硬化物の耐熱性のバランスに優れるステータコア絶縁用樹脂組成物を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639854000001
    Figure 0007639854000001
Patent Text Reader

Abstract

To provide a resin composition for stator core insulation excellent in balance of workability when filled with a resin composition, a filling property of a resin, and a heat resistance of a cured article of the resin.SOLUTION: A resin composition for stator core insulation is a composition used for formation of an insulation member of a stator core having a cyclic stator core material having a plurality of electromagnetic steel sheets laminated, and a plurality of teeth, a coil wound around the plurality of teeth, and an insulation member for insulating the coil from the stator core material, contains an epoxy resin, a curing agent, and an inorganic filler, in which content of the inorganic filler based on total amount of the resin composition for stator core insulation is 50 mass% to 95 mass%, glass transition temperature of a cured article of the resin composition for stator core insulation is 100°C to 350°C, and elastic modulus during heating of the cured article of the resin composition for stator core insulation measured at 150°C is 1 GPa to 50 GPa.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for insulating a stator core. [Background technology]

[0002] A technology for using a resin material in a stator core is described in Patent Document 1 (JP Patent Publication 2003-284277 A). This document describes a rotating electric machine having a stator in which a number of coils are wound at predetermined intervals around a stator core made of laminated electromagnetic steel sheets, a rotor rotatably held relative to the stator, and a cooling frame to which the stator is fixed, in which a highly heat-conductive composite material made of a thermosetting resin having an anisotropic structure in the resin component is arranged in the slots that form the winding portion of the stator, and it is described that this configuration provides a rotating electric machine with good heat dissipation properties that easily transfers heat generated in the coils. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-284277 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the present inventors have conducted research and found that when the resin material described in the above document is used, there is room for improvement in terms of the balance between the workability when filling the resin material, the filling property of the resin, and the heat resistance of the cured resin. [Means for solving the problem]

[0005] According to the present invention, an annular stator core material having a plurality of teeth and formed by laminating a plurality of electromagnetic steel sheets; A coil wound around a plurality of the teeth; an insulating member that insulates the coil from the stator core material; A resin composition for insulating a stator core used to form the insulating member of a stator core comprising: Epoxy resin, A hardener; An inorganic filler; Including, The content of the inorganic filler relative to the total amount of the stator core insulating resin composition is 50% by mass or more and 95% by mass or less, The glass transition temperature of the cured product of the resin composition for insulating a stator core is 100° C. or higher and 350° C. or lower, The resin composition for insulating stator cores is provided, in which the hot elastic modulus of a cured product of the resin composition for insulating stator cores, measured at 150°C, is 1 GPa or more and 50 GPa or less. Effect of the Invention

[0006] According to the present invention, it is possible to obtain a resin composition for insulating stator cores, which has an excellent balance between workability when filling the resin composition, filling properties of the resin, and heat resistance of the cured resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following describes the embodiments. Note that a numerical range of "X to Y" means "X or more and Y or less" unless otherwise specified.

[0008] In this embodiment, the resin composition for stator core insulation (hereinafter also simply referred to as "resin composition") is used to form an insulating member of a stator core which comprises a ring-shaped stator core material made of multiple laminated electromagnetic steel sheets and having multiple teeth, a coil wound around the multiple teeth, and an insulating member that insulates the coil from the stator core material. The resin composition in this embodiment includes an epoxy resin, a curing agent, and an inorganic filler, and the content of the inorganic filler relative to the total amount of the resin composition is 50% by mass or more and 95% by mass or less, the glass transition temperature (Tg) of a cured product of the resin composition is 100° C. or more and 350° C. or less, and the hot elastic modulus of the cured product of the resin composition measured at 150° C. is 1 GPa or more and 50 GPa or less. First, the components of the resin composition will be described below.

[0009] (Epoxy resin) The epoxy resin may be any monomer, oligomer, or polymer having two or more epoxy groups in one molecule, and there are no limitations on the molecular weight or molecular structure. Examples of epoxy resins include bifunctional or crystalline epoxy resins such as biphenyl type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, stilbene type epoxy resins, and hydroquinone type epoxy resins; novolac type epoxy resins such as cresol novolac type epoxy resins, phenol novolac type epoxy resins, and naphthol novolac type epoxy resins; phenol aralkyl type epoxy resins such as phenylene skeleton-containing phenol aralkyl type epoxy resins, biphenylene skeleton-containing phenol aralkyl type epoxy resins, and phenylene skeleton-containing naphthol aralkyl type epoxy resins; trifunctional type epoxy resins such as triphenol methane type epoxy resins and alkyl-modified triphenol methane type epoxy resins; modified phenol type epoxy resins such as dicyclopentadiene-modified phenol type epoxy resins and terpene-modified phenol type epoxy resins; heterocyclic type epoxy resins such as triazine nucleus-containing epoxy resins. These may be used alone or in combination of two or more. From the viewpoint of obtaining preferable fluidity and strength, the epoxy resin preferably contains one or more epoxy resins selected from the group consisting of phenol novolac type epoxy resins and phenol aralkyl type epoxy resins, and more preferably contains a cresol novolac type epoxy resin.

[0010] The content of the epoxy resin in the resin composition may be, for example, 3 mass% or more, preferably 8 mass% or more, more preferably 10 mass% or more, and even more preferably 12 mass% or more, based on the total solid content of the resin composition, from the viewpoint of improving the fluidity of the resin composition and improving the workability and moldability. In addition, from the viewpoint of improving the heat resistance of a cured product formed using the resin composition, the content of the epoxy resin is preferably 30 mass % or less, and more preferably 20 mass % or less, based on the total solid content of the resin composition.

[0011] In this embodiment, the total solid content of the resin composition refers to the non-volatile content in the resin composition, and refers to the remainder excluding volatile components such as water, solvent, etc. In addition, in this embodiment, the content relative to the total amount of the resin composition refers to the content relative to the total solid content of the resin composition excluding the solvent, when a solvent is included.

[0012] The resin composition may further contain a thermosetting resin other than the epoxy resin, such as one or more selected from the group consisting of bismaleimide resin, benzoxazine resin, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, polyurethane resin, diallyl phthalate resin, silicone resin, cyanate resin, polyimide resin, polyamideimide resin, and benzocyclobutene resin. (hardening agent) The curing agent is not limited as long as it is one generally used in resin compositions containing epoxy resins, and examples thereof include phenolic resin-based curing agents, amine-based curing agents, acid anhydride-based curing agents, mercaptan-based curing agents, and other curing agents. Among these, phenolic resin-based curing agents are preferred in terms of the balance of flame resistance, moisture resistance, electrical properties, curability, storage stability, and the like.

[0013] The phenolic resin-based curing agent may be, for example, any one generally used in epoxy resin compositions, and more specifically, one or more selected from the group consisting of novolac resins obtained by condensing or co-condensing phenols such as phenol novolac resins and cresol novolac resins with formaldehyde or ketones under an acid catalyst; phenol aralkyl resins having a phenylene skeleton synthesized from the above-mentioned phenols and dimethoxyparaxylene or bis(methoxymethyl)biphenyl; phenol aralkyl resins such as phenol aralkyl resins having a biphenylene skeleton; and phenolic resins having a trisphenylmethane skeleton. The phenolic resin-based curing agent is preferably a phenol novolac resin.

[0014] When the curing agent is a phenolic resin-based curing agent, the equivalent ratio between the epoxy resin and the curing agent, i.e., the ratio of (the number of moles of epoxy groups in the epoxy resin / the number of moles of phenolic hydroxyl groups in the phenolic resin-based curing agent) is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.8 or more, from the viewpoint of improving the moldability and reliability of the resin composition. From the same viewpoint, the above ratio is preferably 2 or less, more preferably 1.8 or less, and even more preferably 1.5 or less.

[0015] Examples of the amine curing agent include one or more selected from the group consisting of aliphatic polyamines such as diethylenetriamine (DETA), triethylenetetramine (TETA), and metaxylylenediamine (MXDA); aromatic polyamines such as diaminodiphenylmethane (DDM), m-phenylenediamine (MPDA), and diaminodiphenylsulfone (DDS); and polyamine compounds including dicyandiamide (DICY) and organic acid dihydralazide.

[0016] Examples of the acid anhydride curing agent include one or more selected from the group consisting of alicyclic acid anhydrides such as hexahydrophthalic anhydride (HHPA), methyltetrahydrophthalic anhydride (MTHPA), and maleic anhydride; and aromatic acid anhydrides such as trimellitic anhydride (TMA), pyromellitic anhydride (PMDA), benzophenonetetracarboxylic acid (BTDA), and phthalic anhydride.

[0017] Examples of the mercaptan-based curing agent include one or more selected from the group consisting of trimethylolpropane tris(3-mercaptobutyrate) and trimethylolethane tris(3-mercaptobutyrate).

[0018] Examples of other curing agents include one or more selected from the group consisting of isocyanate compounds such as isocyanate prepolymers and blocked isocyanates; and organic acids such as carboxylic acid-containing polyester resins. Furthermore, two or more different types of curing agents from the above may be used in combination.

[0019] The content of the curing agent in the resin composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more, based on the total amount of the resin composition, from the viewpoint of realizing excellent fluidity during molding and improving filling properties and moldability. On the other hand, from the viewpoint of improving the moisture resistance reliability and heat resistance of the cured product, the content of the curing agent is preferably 20 mass % or less, more preferably 15 mass % or less, even more preferably 10 mass % or less, and even more preferably 5 mass % or less, based on the total amount of the resin composition.

[0020] (Inorganic filler) Examples of inorganic fillers include one or more selected from the group consisting of fused silica such as fused crushed silica and fused spherical silica, silica such as crystalline silica, alumina, aluminum hydroxide, silicon nitride, and aluminum nitride. From the viewpoint of obtaining favorable mechanical properties or thermal properties of the cured product of the resin composition, the inorganic filler preferably contains silica, and more preferably contains one or more types selected from the group consisting of crushed silica and fused spherical silica.

[0021] From the viewpoint of improving the fluidity and moldability of the resin composition, the average particle size d50 of the inorganic filler is preferably 0.01 μm or more, more preferably 1 μm or more, and further preferably 5 μm or more. Moreover, from the viewpoint of improving the filling property and suppressing the occurrence of unfilled portions, the average particle size d50 of the inorganic filler is preferably 50 μm or less, and more preferably 40 μm or less.

[0022] In addition, two or more fillers having different average particle diameters d50 may be used in combination as the inorganic filler. This makes it possible to more effectively increase the filling ability of the inorganic filler relative to the total solid content of the resin composition. For example, from the viewpoint of improving the filling ability of the resin composition, the inorganic filler preferably includes a first filler having an average particle diameter of 1 μm or more and 12 μm or less, and a second filler having an average particle diameter of more than 12 μm and 30 μm or less. From the same viewpoint, the inorganic filler may include, for example, a first filler having an average particle diameter of 0.01 μm or more and 1 μm or less, and a second filler having an average particle diameter of more than 1 μm and 50 μm or less.

[0023] From the viewpoint of improving the fluidity of the resin composition, the (d50 / d90) value calculated from the particle diameter d90 of the inorganic filler having a cumulative frequency of 90% measured using a laser diffraction particle size distribution analyzer and the average particle diameter d50 of the inorganic filler is preferably 0.2 or more, more preferably 0.25 or more, and even more preferably 0.3 or more. Moreover, from the viewpoint of improving the narrow portion filling ability, the above ratio (d50 / d90) is preferably 1.0 or less, more preferably 0.9 or less, and further preferably 0.8 or less.

[0024] Here, the particle size of the inorganic filler, specifically d50 and d90, can be obtained by measuring the particle size distribution of the particles on a volume basis using a commercially available laser diffraction particle size distribution measuring device (e.g., SALD-7000, manufactured by Shimadzu Corporation).

[0025] The content of the inorganic filler in the resin composition is preferably 50% by mass or more, more preferably 65% ​​by mass or more, and even more preferably 80% by mass or more, based on the total amount of the resin composition, from the viewpoints of improving low moisture absorption and low thermal expansion properties and more effectively improving the temperature cycle resistance and reflow resistance of the cured product of the resin composition. In addition, from the viewpoint of more effectively improving the fluidity and filling property during molding of the resin composition, the content of the inorganic filler is preferably 95 mass % or less, and more preferably 93 mass % or less, based on the total amount of the resin composition.

[0026] In addition, when the inorganic filler contains silica, the content of silica in the resin composition is preferably 50 mass % or more, more preferably 65 mass % or more, and even more preferably 80 mass % or more, based on the total amount of the resin composition, from the viewpoints of improving low moisture absorption and low thermal expansion, and more effectively improving the temperature cycle resistance and reflow resistance of the cured product of the resin composition. From the viewpoint of more effectively improving the fluidity and filling property of the resin composition during molding, the content of silica in the resin composition is preferably 95% by mass or less, and more preferably 93% by mass or less.

[0027] In the present embodiment, the resin composition may further include components other than the above-mentioned components. For example, the resin composition may further include a release agent. The release agent may contain one or more types selected from the group consisting of natural waxes such as carnauba wax; synthetic waxes such as montanic acid ester wax, diethanolamine-dimontanic acid ester, and tolylene diisocyanate-modified oxidized wax; higher fatty acids such as zinc stearate and metal salts thereof; and paraffin, and is preferably carnauba wax.

[0028] When the resin composition contains a mold release agent, the content thereof is preferably 0.05 mass % or more, and more preferably 0.1 mass % or more, based on the total amount of the resin composition, from the viewpoint of releasability from a mold during resin molding. From the viewpoint of adhesion to each member, the content of the release agent is preferably 3% by mass or less, and more preferably 1% by mass or less, based on the total amount of the resin composition.

[0029] The resin composition may also contain one or more additives selected from the group consisting of curing accelerators, coupling agents, flame retardants, ion scavengers, colorants, stress reducing agents, and antioxidants.

[0030] The curing accelerator may be any accelerator that accelerates the crosslinking reaction between the epoxy resin and the curing agent, and any accelerator that is generally used in epoxy resin compositions may be used. The curing accelerator may include one or more selected from the group consisting of diazabicycloalkenes and derivatives thereof, such as 1,8-diazabicyclo(5,4,0)undecene-7; organic phosphines, such as triphenylphosphine and methyldiphenylphosphine; imidazole compounds (imidazole curing accelerators), such as 2-methylimidazole; and tetra-substituted phosphonium and tetra-substituted borates, such as tetraphenylphosphonium and tetraphenylborate.

[0031] Examples of the imidazole-based curing accelerator include imidazole, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and 1-cyanoethyl-2-phenylimidazolium trimethylolate. The compound includes one or more selected from the group consisting of melitate, 2,4-diamino-6-[2'-methylimidazolyl(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4-methylimidazolyl(1')]-ethyl-s-triazine, an isocyanuric acid adduct of 2,4-diamino-6-[2'-methylimidazolyl(1')]-ethyl-s-triazine, an isocyanuric acid adduct of 2-phenylimidazole, an isocyanuric acid adduct of 2-methylimidazole, 2-phenyl-4,5-dihydroxydimethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole.

[0032] As the coupling agent, for example, various silane-based compounds such as epoxysilane, mercaptosilane, aminosilane, alkylsilane, ureidosilane, vinylsilane, methacrylsilane, titanium-based compounds, aluminum chelates, aluminum / zirconium-based compounds, and other known coupling agents can be used. Examples of these include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-anilinopropyltrimethoxysilane, γ-anilinopropylmethyldimethoxysilane, γ-[bis(β-hydroxyethyl)]aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyl N-(vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, N-(vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane, N-(vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane, phenylaminopropyltrimethoxysilane, γ-(β-aminoethyl)aminopropyldimethoxymethylsilane, N-(trimethoxysilylpropyl)ethylenediamine, N-(dimethoxymethylsilylisopropyl)ethylenediamine, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, N-(vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, hexamethyldisilane, vinyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-triethoxysilyl-N-(1,Silane coupling agents such as hydrolyzate of 3-dimethyl-butylidene)propylamine, isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate Examples of titanate-based coupling agents include ethylene titanate, bis(dioctyl pyrophosphate) titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and tetraisopropyl bis(dioctyl phosphite) titanate. These may be used alone or in combination of two or more. Among these, silane-based compounds such as epoxy silane, mercapto silane, amino silane, alkyl silane, ureido silane, or vinyl silane are more preferred. In addition, from the viewpoint of more effectively improving filling properties and moldability, it is even more preferred to use secondary amino silanes such as phenyl aminopropyl trimethoxy silane.

[0033] From the viewpoint of obtaining favorable fluidity of the resin composition, the content of the coupling agent is preferably 0.05% by mass or more, and more preferably 0.10% by mass or more, based on the total solid content of the resin composition. Furthermore, from the viewpoint of improving the mechanical strength of the cured product of the resin composition, the content of the coupling agent is preferably 1.5 mass % or less, more preferably 1.0 mass % or less, and even more preferably 0.5 mass % or less, based on the total solid content of the resin composition.

[0034] The flame retardant may include, for example, one or more selected from the group consisting of aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, and phosphazene.

[0035] The ion scavenger can include one or more selected from the group consisting of hydrotalcite and aluminum-magnesium-based inorganic ion exchangers.

[0036] The colorant may include one or more types selected from the group consisting of carbon black, red iron oxide, and titanium oxide, and preferably includes carbon black.

[0037] The content of the colorant is preferably 0.05% by mass or more, and more preferably 0.10% by mass or more, based on the total amount of the resin composition, from the viewpoint of providing a preferable appearance to the cured product of the resin composition. From the viewpoint of obtaining a preferable resin viscosity, the content of the colorant is preferably 1.5 mass % or less, more preferably 1.0 mass % or less, and further preferably 0.5 mass % or less, based on the total amount of the resin composition.

[0038] The stress reducing agent can include one or more selected from the group consisting of silicone oil, silicone rubber, polyisoprene, polybutadienes such as 1,2-polybutadiene and 1,4-polybutadiene, styrene-butadiene rubber, acrylonitrile-butadiene rubber, polychloroprene, thermoplastic elastomers such as poly(oxypropylene), poly(oxytetramethylene) glycol, polyolefin glycol, poly-ε-caprolactone, polysulfide rubber, and fluororubber.

[0039] Next, the characteristics of the resin composition or the cured product thereof will be described. The gel time of the resin composition is preferably 10 seconds or more, and more preferably 20 seconds or more, from the viewpoint of improving the moldability of the resin composition and accelerating the molding cycle. In order to realize a cured product with excellent curability, the gel time of the resin composition is preferably 60 seconds or less, and more preferably 50 seconds or less. The gel time can be measured by melting the resin composition on a hot plate heated to 175° C., and then kneading the composition with a spatula while measuring the time it takes for the composition to become tack-free (gel time).

[0040] The glass transition temperature of the cured product of the resin composition is 100° C. or higher, preferably 140° C. or higher, and more preferably 150° C. or higher, from the viewpoint of improving heat resistance. From the viewpoint of improving the toughness of the cured product, the glass transition temperature of the cured product of the resin composition is 300° C. or lower, preferably 270° C. or lower, and more preferably 250° C. or lower. Here, the glass transition temperature of the cured product is measured using a thermomechanical analyzer (TMA) under conditions of a measurement temperature range of 0° C. to 320° C. and a temperature rise rate of 5° C. / min.

[0041] The hot elastic modulus of the cured product of the resin composition measured at 150° C. is 1 GPa or more, preferably 1.2 GPa or more, and more preferably 1.4 GPa or more, from the viewpoint of increasing the strength of the cured product. From the viewpoint of obtaining favorable stress relaxation properties of the cured product, the above-mentioned hot elastic modulus is 50 GPa or less, preferably 40 GPa or less, and more preferably 30 GPa or less. The hot elastic modulus of the cured product is measured, for example, in accordance with JIS K 7171.

[0042] The dielectric constant (ε r ) is preferably 4.4 or less, and more preferably 4.3 or less, from the viewpoint of improving the insulating properties of the cured product. In addition, the above relative dielectric constant (ε r The lower limit of may be, for example, 2.0 or more, and preferably 2.5 or more. The dielectric constant of the cured product at 1 MHz (ε r ) is measured, for example, in accordance with JIS K 6911.

[0043] The linear expansion coefficient (CTE1) of the cured product of the resin composition at or below the glass transition temperature is preferably 8 ppm / °C or more, and more preferably 9 ppm / °C or more, from the viewpoint of reducing the linear expansion coefficient of the cured product during thermal history. Moreover, from the viewpoint of suppressing residual stress in the cured product, the above CTE1 is preferably 30 ppm / °C or less, and more preferably 25 ppm / °C or less. Here, CTE1 is measured using a TMA device under a load of 2 g to 10 g.

[0044] Next, the state of the resin composition is preferably solid from the viewpoint of improving workability. From the same viewpoint, the form of the resin composition is preferably powder, granules, tablets, or sheets.

[0045] Next, a method for producing the resin composition will be described. For example, first, the above-mentioned raw material components are mixed by a known means to obtain a mixture. The mixture is then melt-kneaded to obtain a kneaded product. As a kneading method, for example, an extrusion kneader such as a single-screw kneading extruder or a twin-screw kneading extruder, or a roll-type kneader such as a mixing roll can be used, but it is preferable to use a twin-screw kneading extruder. After cooling, the kneaded product can be made into a desired shape such as powder, granules, tablets, or sheets.

[0046] As a method for obtaining a powdered resin composition, for example, a method of crushing the kneaded material with a crushing device can be mentioned. The kneaded material may be formed into a sheet and crushed. As the crushing device, for example, a hammer mill, a stone grinding machine, a roll crusher, etc. can be used.

[0047] As a method for obtaining a granular or powdery resin composition, for example, a granulation method represented by a hot-cut method in which a die having a small diameter is provided at the outlet of a kneading device and the molten kneaded material discharged from the die is cut to a predetermined length with a cutter, etc., can be used. In this case, after obtaining a granular or powdery resin composition by a granulation method such as the hot-cut method, it is preferable to perform degassing before the temperature of the resin composition drops too much.

[0048] The resin composition obtained in this embodiment contains an epoxy resin, a curing agent, and an inorganic filler, and the content of the inorganic filler, the glass transition temperature of the cured product, and the hot elastic modulus of the cured product are each within the specific ranges described above. Therefore, the resin composition can be suitably used as a resin composition for insulating stator cores, and a cured product for insulating stator cores can be obtained that has excellent workability when filling the resin composition, excellent filling ability of the resin, and excellent thermal history resistance of the cured product.

[0049] As described above, the stator core is equipped with a coil, and the coil is preferably made of a metal containing copper and a polymer containing nitrogen, from the viewpoint of obtaining excellent electrical conductivity, and is more preferably a resin-coated copper coil.

[0050] The present invention has been described above based on the embodiments, but the present invention is not limited to the above embodiments, and the configuration can be changed without departing from the gist of the present invention. Below, examples of reference forms are given. 1. An annular stator core material having a plurality of teeth and made of a plurality of laminated electromagnetic steel sheets; A coil wound around a plurality of the teeth; an insulating member that insulates the coil from the stator core material; A resin composition for insulating a stator core used to form the insulating member of a stator core comprising: Epoxy resin, A hardener; An inorganic filler; Including, The content of the inorganic filler relative to the total amount of the stator core insulating resin composition is 50% by mass or more and 95% by mass or less, The glass transition temperature of the cured product of the resin composition for insulating a stator core is 100° C. or higher and 350° C. or lower, A resin composition for insulating stator cores, the cured product of which has a hot elastic modulus of 1 GPa or more and 50 GPa or less, measured at 150°C. 2. The inorganic filler comprises silica; 2. The resin composition for insulating stator cores according to 1., wherein the content of the silica relative to the total amount of the resin composition for insulating stator cores is 50 mass % or more and 95 mass % or less. 3. A resin composition for insulating stator cores according to 1. or 2., wherein the gel time of the resin composition for insulating stator cores is 10 seconds or more and 60 seconds or less. 4. The dielectric constant (ε r 4. The resin composition for insulating a stator core according to any one of 1. to 3., wherein the thermal expansion coefficient (Tc) is 4.4 or less. 5. A resin composition for insulating stator cores according to any one of 1 to 4, wherein the linear expansion coefficient (CTE1) of the cured product of the resin composition for insulating stator cores at a temperature equal to or lower than the glass transition temperature is 8 ppm / °C or more and 30 ppm / °C or less. 6. The resin composition for insulating a stator core according to any one of 1. to 5., further comprising a release agent. 7. A resin composition for insulating stator cores according to any one of 1. to 6., wherein the resin composition for insulating stator cores is in the form of powder, granules, tablets or sheets. 8. A resin composition for insulating a stator core according to any one of 1. to 7., wherein the inorganic filler contains crushed silica. 9. A resin composition for insulating stator cores described in any one of 1. to 8., wherein the d50 / d90 value calculated for the inorganic filler from the particle diameter d90 of the inorganic filler at a cumulative frequency of 90% measured using a laser diffraction particle size distribution analyzer and the average particle diameter d50 of the inorganic filler is 0.2 or more and 1.0 or less. 10. A resin composition for insulating stator cores according to any one of 1. to 9., wherein the resin composition for insulating stator cores is solid. 11. A resin composition for insulating a stator core according to any one of 1. to 10., wherein the coil is made of a metal containing copper and a polymer containing nitrogen. 12. The resin composition for insulating a stator core according to claim 11, wherein the coil is a resin-coated copper coil. EXAMPLES

[0051] The present invention will be described in detail below using examples, but the present invention is not limited to the descriptions of these examples.

[0052] The raw material components used in each of the Examples and Comparative Examples are shown below. Epoxy resin 1: YDCN-800-55 (manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.), cresol novolac type epoxy resin Hardener 1: PR-HF-3 (Sumitomo Bakelite Co., Ltd.), phenol novolac resin Inorganic filler 1: F-115 (manufactured by Fumitec), crushed silica, d50 = 15 μm, (d50 / d90) = 0.3 Inorganic filler 2: FB-105 (manufactured by Denka), fused spherical silica, d50=10 μm, (d50 / d90)=0.34 Colorant 1: Carbon black (Mitsubishi Chemical, Carbon #5) Coupling agent 1: Phenylaminopropyltrimethoxysilane (Toray Dow Corning Co., Ltd., CF4083) Release agent 1: Carnauba wax (Nikko Fine Co., Ltd., Nikko Carnauba)

[0053] (Preparation of Resin Composition) First, the raw materials formulated according to Table 1 were mixed at room temperature using a mixer, and then roll-kneaded at 70° C. to 110° C. Next, the resulting kneaded product was cooled and then pulverized to obtain a resin composition.

[0054] The inorganic fillers used in the examples and the resulting resin compositions were subjected to the following measurements. The measurement results are shown in Table 1. (d50 and (d50 / d90) of inorganic fillers) The measurement was performed using a laser particle sizer (Shimadzu Corporation, SALD-7000).

[0055] (Gel Time) Each resin composition was melted on a hot plate heated to 175° C., then kneaded and stirred with a spatula to harden it, and the time until it became tack-free (gel time) was measured.

[0056] (Dielectric constant (εr) of cured product at 1 MHz) Using a low pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.), the resin composition of each example was injected and molded at a mold temperature of 175°C, an injection pressure of 10 MPa, and a curing time of 120 seconds to prepare a 50 mm disk-shaped test piece. The relative dielectric constant of each test piece was measured at a frequency of 1 MHz using a Q meter.

[0057] (CTE1 of cured product) The resin composition was injected into a low-pressure transfer molding machine (KTS-15, manufactured by Kotaki Seiki Co., Ltd.) at a mold temperature of 175°C, injection pressure of 10 MPa, and curing time of 120 seconds to prepare test pieces of 10 mm x 4 mm x 4 mm. The CTE1 of each test piece was measured with a TMA device under the conditions of a measurement temperature range of 0°C to 320°C and a heating rate of 5°C / min.

[0058] (Tg) First, the epoxy resin composition was injected and molded using a transfer molding machine at a mold temperature of 140°C (each example) and 175°C (each comparative example), injection pressure of 9.8MPa, and curing time of 3 minutes to obtain a test piece of 10mm x 4mm x 4mm. Next, the obtained test piece was post-cured at 140°C (each example) and 175°C (each comparative example) for 4 hours, and then measured using a thermomechanical analyzer (manufactured by SII, TMA / SS6100) under the conditions of a measurement temperature range of 0°C to 320°C and a heating rate of 5°C / min. From the measurement results, the glass transition temperature was calculated.

[0059] (Hot elastic modulus) For the resin compositions of each Example and Comparative Example, first, the resin composition was injected and molded using a low pressure transfer molding machine (KOTAKISEIKI KTS-15) at a mold temperature of 175°C, injection pressure of 9.8MPa, and curing time of 180 seconds to obtain test pieces of 10mm x 80mm x 4mm. Next, the obtained test pieces were post-cured at 175°C for 4 hours, and then measured using a dynamic viscoelasticity measuring device (A&D RHEOVIBRON (registered trademark) DDV-25GP) under conditions of a measurement temperature range of 20°C to 300°C and a heating rate of 5°C / min to measure the elastic modulus at 175°C.

[0060] (Method of evaluating resin composition) The resin compositions obtained in each example were evaluated for workability during filling, occurrence of unfilled areas and voids ("Unfilled / Voids" in Table 1), and condition after heat history (cracks / peeling) according to the following evaluation criteria. The evaluation results are also shown in Table 1.

[0061] (Workability, unfilled and void occurrence) The evaluation criteria are as follows: ○: Good △:Partially unfilled ×: Not filled (Workability) The evaluation criteria are as follows: 〇: Good workability △: Poor workability ×: Poor workability

[0062] (Condition after heat history (cracks / peeling)) The resin-filled portion was cut out, and the cross section was observed under a microscope. ○: Good △: Some cracks and peeling ×: Cracks and peeling

[0063] [Table 1]

[0064] As can be seen from Table 1, the resin composition of each Example enabled the production of a cured product that was excellent in workability when filling the resin composition, suppression of unfilled portions and voids, and a balance of the state after thermal history.

Claims

1. an annular stator core material having a plurality of teeth and formed by laminating a plurality of electromagnetic steel sheets; A coil wound around a plurality of the teeth; an insulating member that insulates the coil from the stator core material; A resin composition for insulating a stator core used to form the insulating member of a stator core comprising: Epoxy resin, A hardener; An inorganic filler; A coupling agent; Including, The epoxy resin comprises a cresol novolac type epoxy resin, the curing agent comprises a phenolic novolac resin; the inorganic filler comprises silica; The content of the inorganic filler relative to the total amount of the resin composition for insulating a stator core is 50% by mass or more and 95% by mass or less, The content of the epoxy resin relative to the total amount of the stator core insulating resin composition is 3 mass% or more and 30 mass% or less, The content of the curing agent relative to the total amount of the stator core insulating resin composition is 1 mass% or more and 15 mass% or less, The glass transition temperature of the cured product of the resin composition for insulating a stator core is 100° C. or higher and 350° C. or lower, The hot elastic modulus of the cured product of the resin composition for insulating a stator core, measured at 150° C., is 1 GPa or more and 50 GPa or less, the coupling agent comprises a secondary aminosilane; The coil is made of a metal containing copper and a polymer containing nitrogen, A resin composition for insulating a stator core, except when the resin composition for insulating a stator core further contains a curing accelerator, the curing accelerator being an imidazole compound.

2. A resin composition for insulating stator cores as described in claim 1, wherein the content of the silica relative to the total amount of the resin composition for insulating stator cores is 50 mass% or more and 95 mass% or less.

3. 3. The resin composition for insulating stator cores according to claim 1, wherein the gel time of the resin composition for insulating stator cores is 10 seconds or more and 60 seconds or less.

4. The dielectric constant (ε r 4. The resin composition for insulating a stator core according to claim 1 , wherein the viscosity coefficient of the resin composition is 4.4 or less.

5. The resin composition for insulating a stator core according to any one of claims 1 to 4, wherein the linear expansion coefficient (CTE1) of the cured product of the resin composition for insulating a stator core at a temperature equal to or lower than the glass transition temperature is 8 ppm / °C or more and 30 ppm / °C or less.

6. The resin composition for insulating a stator core according to claim 1 , further comprising a mold release agent.

7. The resin composition for insulating a stator core according to claim 1 , wherein the resin composition for insulating a stator core is in the form of powder, granules, a tablet or a sheet.

8. The resin composition for insulating a stator core according to claim 1 , wherein the inorganic filler contains crushed silica.

9. The inorganic filler has a particle diameter d90 value of the inorganic filler at which the cumulative frequency measured on a volume basis using a laser diffraction particle size distribution measuring device is 90%, and the inorganic filler has a d50 value. The d50 / d90 value calculated from the particle diameter d90 value of the inorganic filler at which the cumulative frequency measured on a volume basis using a laser diffraction particle size distribution measuring device is 90% is 0.2 or more and 1.0 or less. The resin composition for insulating stator cores according to any one of claims 1 to 8.

10. The resin composition for insulating a stator core according to claim 1 , wherein the resin composition for insulating a stator core is in a solid state.

11. The resin composition for insulating a stator core according to claim 1 , wherein the coil is a resin-coated copper coil.

Citation Information

Patent Citations

  • Epoxy resin composition for molding, molded product made using the same for high-voltage apparatus, and production thereof

    JP1995242732A

  • Electric rotating machine and its manufacturing method

    JP2003284277A

  • Insulated wire, and electric coil and motor using the same

    JP2012243614A

  • Square electric wire for motor winding of vehicle / ship, wound coil, and motor

    WO2014141322A1

  • Epoxy resin composition and structure

    WO2018083885A1